Corporate government practices and environmental reporting of companies in Malaysia : finding possibilities of doubles thumbs up. - Sharifah Buniamin; Bakhtiar Alrazi; Nor Hasimah Johari; Noor Raida Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2011)
Demontrating good corporate governance and maintaining sound environmental performance are among the key challenges facing teh organisation to ensure its sustainability. In an attempt to investigate the linkage between these two essential aspects, this study scrutinises the annual reports of 243 companies listed on the Main Board of Bursa Malaysia. These are six selected corparate government attributes namely, board independence, CEO duality, management ownership, board size,financial expert and meeting frequency. Overall, it was found that the existence of environmentalreporting is low. Only 28% of the companies disclosed environmental information. Furthermore, on average, each company reported 4.7 sentences, while the quality, as measured by the disclosure index shows an average of 3.24. The most significant corporate governance attributes in influencing the extent of environmental reporting are board size and management ownership. The finding provide limited evidence to support that, companies which comply with corporate governance practice have the tendencies to be more environmentally reponsible.